Modelling the operations of a circular economy fashion start-up - de Olañeta, Javier; Patsavellas, John; Salonitis, Konstantinos (Elsevier, 2024)
This paper presents a case study of Pantala, a fashion start-up, intending to operationalise a circular supply of luxury womenswear through a monthly subscription-fee model. To optimize the company's cashflow and ensure success, the operational flows were modelled and analysed through discrete-event simulation techniques, with a focus on inventory management and minimizing operational costs. Simulation results demonstrated a high level of accuracy in predicting system performance, with an average relative error of less than 5% for most performance indicators. Insights are provided into the benefits of using simulation modelling for operational planning and optimization of complex systems, especially in the case of start-ups.
Presented at: 56th CIRP International Conference on Manufacturing Systems 2023, 24-26 October 2023, Cape Town, South Africa
Keywords: start-up; circular fashion; discrete-event simulation; e-tailingfast-fashion; reverse logistics